2009 IEEE International Conference on Robotics and Automation 2009
DOI: 10.1109/robot.2009.5152694
|View full text |Cite
|
Sign up to set email alerts
|

Minimalistic control of a compass gait robot in rough terrain

Abstract: Abstract-Although there has been an increasing interest in dynamic bipedal locomotion for significant improvement of energy efficiency and dexterity of mobile robots in the real world, their locomotion capabilities are still mostly restricted on flat surfaces. The difficulty of dynamic locomotion in rough terrain is mainly originated in the stability and controllability of gait patterns while exploiting the natural mechanical dynamics of the robots. For a systematic investigation of the challenging problem, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Ogino et al (2008) developed a walking controller that enables a robot to walk on rough terrain by changing the compliance of the joints without sensing the state of the surface of the ground. Iida and Tedrake (2009) presented a minimalistic control architecture with a minimum sensory feedback of a compass gait model for dynamic bipedal walking on the different inclinations of slope.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Ogino et al (2008) developed a walking controller that enables a robot to walk on rough terrain by changing the compliance of the joints without sensing the state of the surface of the ground. Iida and Tedrake (2009) presented a minimalistic control architecture with a minimum sensory feedback of a compass gait model for dynamic bipedal walking on the different inclinations of slope.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In Yang et al (2009), stability of aperiodic walking motions was studied via the virtual-constraints and hybrid zero dynamics approach which achieves stability via high-gain feedback (Grizzle et al, 2001;Westervelt et al, 2003Westervelt et al, , 2007. The problem of footstep planning has been approached using computational optimal control (Byl and Tedrake, 2009) and experimental studies have shown that a minimalistic open-loop control can achieve stability for the compassgait walker (Iida and Tedrake, 2009). Recently, more complete planning and control systems have been developed for quadruped walkers -see e.g.…”
Section: Bipedal Walking Robotsmentioning
confidence: 99%
“…Initial intuitive controllers for complex terrain [15] were followed by more careful consideration of walking dynamics [38], leading to optimal control methods for rough terrain traversal [7], [27]. Recent results in this area recognize that trajectory stability on rough terrain is difficult to define [8] but exploit reduced dimension projections of walking dynamics to coordinate frames to which desired trajectories are transversal to achieve formally established stability properties [18], [31].…”
Section: Related Workmentioning
confidence: 99%
“…whose solution for θ, in conjunction with (27), yields the solution for k through the identity tan 2 θ + 1 = 1/ cos 2 θ as…”
Section: B Ball-hopper Model 1) System Dynamicsmentioning
confidence: 99%